2011
DOI: 10.1016/j.acvd.2011.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C levels are associated with the prognosis of systolic heart failure patients

Abstract: Cystatin C, together with hs-CRP and homocysteine, is an independent risk factor that is important in the prognosis of patients with systolic heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…Interestingly, Naruse et al[28] found the best relationship between high levels of cystatin-C and the risk of cardiac death in patients with acute HF and an eGFR calculated by the MDRD formula between 44 and 79 ml/min/1.73 m 2 , independent of volemia and body weight. Cystatin-C was also an independent predictor of prognosis at 2 years of follow-up for the occurrence of death, heart transplantation, or readmission due to worsening HF in 138 systolic HF patients admitted for acute descompensation [29].…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, Naruse et al[28] found the best relationship between high levels of cystatin-C and the risk of cardiac death in patients with acute HF and an eGFR calculated by the MDRD formula between 44 and 79 ml/min/1.73 m 2 , independent of volemia and body weight. Cystatin-C was also an independent predictor of prognosis at 2 years of follow-up for the occurrence of death, heart transplantation, or readmission due to worsening HF in 138 systolic HF patients admitted for acute descompensation [29].…”
Section: Discussionmentioning
confidence: 95%
“…This protein has a low molecular weight and does not form a complex with other secreted proteins in the blood [28]. Cystatin-C independently predicts adverse events in chronic HF and is also an independent risk factor in the prognosis of patients with HF [29]. Shlipak et al [30] showed the prognostic value of cystatin-C instable HF patients who had lower EF < 35%.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple small clinical studies have demonstrated that blood homocysteine levels are elevated in patients with heart failure compared to control population [81,82,83,84]. Blood homocysteine level is also related to the clinical severity of heart failure [85].…”
Section: Methionine-homocysteine Cycle Folate Metabolism and Heamentioning
confidence: 99%